Targeting gastrointestinal stromal tumor with 68Ga-labeled peptides: an in vitro study on gastrointestinal stromal tumor-cell lines - Paulmichl, Achim; Wängler, Björn (Cancer biotherapy and radiopharmaceuticals, 2016)
The gastrointestinal stromal tumor (GIST) is a rare disease with limited therapeutic options when resistance to tyrosine kinase inhibitor (TKI) treatment occurs. The authors investigated binding of various 68Ga-labeled peptides, targeting receptors reported to be overexpressed in GIST, in different cell lines. For this purpose, three GIST cell lines were tested: GIST-T1, GIST882 (Imatinib sensitive), and GIST430 (Imatinib resistant). DOTA-NT 8-13 (targeting NTR1), DOTA-TATE (targeting SSTR2), CP04 (a minigastrin derivative targeting CCK2-R), VIP-DOTA (targeting VPAC2-R), and 2 DOTA-bombesin derivatives [targeting gastrin releasing peptide receptors (GRPR)] were radiolabeled with 68Ga and incubated with the respective tumor cell and control cell lines. Membrane-bound and internalized activity was measured. Very low or no specific binding to GIST cells was found for all 68Ga-labeled DOTA peptides except for bombesin derivatives indicating no or very low expression of respective receptors. Related to GRPR a pronounced specific binding to all GIST cell lines with no preference related to TKI resistance status was found, both for an agonist (AMBA) with high internalization and for an antagonist (NeoBOMB1) with mainly membrane-bound activity (with up to >80% bound/mg protein). GRPR expression was confirmed by immunohistochemistry. The results show that radiolabeled bombesin analogues, especially antagonists are very promising candidates for targeting GIST.